2021
DOI: 10.1088/2631-6331/ac3ddc
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering for design of novel 2D cobalt sulfide-Mxene heterostructured catalyst toward alkaline water splitting

Abstract: In this work, we used an interfacial engineering method to investigate a novel hybrid of two-dimensional cobalt sulfide-Mxene (2D CoS-Mo2TiC2) heterostructure supported by a three-dimensional foam substrate. The modification electronic properties caused by unique interfacial interactions resulted in a significant increase in the number of electroactive sites and charge transfer ability, thereby accelerating kinetics of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an alkaline medium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…These results suggest that enriched heterogeneous interfaces could enhance catalysts' kinetics and electrochemical performances for OER. [70] Electrochemically active surface area (ECSA) was used to examine the utilization of catalysts by measuring their active surface areas which contact an electrolyte. To obtain the ECSA of the as-prepared catalyst, we performed CV with different scan rates ranging from 10 to 100 mV s −1 at a potential of 1.22 to 1.32 V versus RHE (Figure S14, Supporting Information) and derived current at a middle potential value from CV curves.…”
Section: Oer Performancementioning
confidence: 99%
“…These results suggest that enriched heterogeneous interfaces could enhance catalysts' kinetics and electrochemical performances for OER. [70] Electrochemically active surface area (ECSA) was used to examine the utilization of catalysts by measuring their active surface areas which contact an electrolyte. To obtain the ECSA of the as-prepared catalyst, we performed CV with different scan rates ranging from 10 to 100 mV s −1 at a potential of 1.22 to 1.32 V versus RHE (Figure S14, Supporting Information) and derived current at a middle potential value from CV curves.…”
Section: Oer Performancementioning
confidence: 99%
“…v) The hierarchical structure without aggregation promotes long-term durability by facilitating a higher exposure of active sites to the electrolyte. [162,230] Apart from sulfides, other chalcogenides, such as metal selenides were also combined with MXene to improve the overall OER activity. It is observed that SSA, charge transfer kinetics, and OER activity of the catalyst increased after adding Ti 3 C 2 T x to selenides.…”
Section: Transition Metal Chalcogenides Loaded On Mxene Supportsmentioning
confidence: 99%
“…Current catalyst design has the critical challenge of attaining a simplified system construction having multifunctionality, while sustaining high-level activity with promising overall performance and more economical viability. Recently, the idea of developing a multifunctional electrocatalyst derived from the unique combination of at least two active materials has been expected to be able to effectively overcome the issues mentioned above. Such an approach can further reduce the effective loading of each active material and the complication of electrode fabrication, thereby efficiently extending the application scope of the catalyst and enabling it to be more economically viable. In particular, since two active metal materials are decreased in size from nano/clusters to a well-dispersed single atom (SA) state, there is an effective increase of the low-coordination metal sites having a fine-tuned electronic structure for selective drive-specific multielectron reactions with high catalytic properties, while potentially providing 100% site utilization. In this context, dual SAs can provide two sites enabling independent binding energies toward each reactant in different catalytic reactions. In addition, their specific assembly within the host material, whether in in-plane, bridged, or cofacial form, may also effectively improve selectivity for certain reactions. , Despite their superior electrocatalytic activities, it is difficult to achieve a controlled synthesis method to maintain high loading of individual metal atoms because of their low structural stability arising from high surface energy and weak interactions between SAs and supporting material.…”
Section: Introductionmentioning
confidence: 99%